Surface curvature in triply-periodic minimal surface architectures as a distinct design parameter in preparing advanced tissue engineering scaffolds. (12th April 2017) - Blanquer, Sébastien B G; Werner, Maike; Hannula, Markus; Sharifi, Shahriar; Lajoinie, Guillaume P R; Eglin, David; Hyttinen, Jari; Poot, André A; Grijpma, Dirk W
Abstract: Reproduction of the anatomical structures and functions of tissues using cells and designed 3D scaffolds is an ongoing challenge. For this, scaffolds with appropriate biomorphic surfaces promoting cell attachment, proliferation and differentiation are needed. In this study, eight triply-periodic minimal surface (TPMS)-based scaffolds were designed using specific trigonometric equations, providing the same porosity and the same number of unit cells, while presenting different surface curvatures. The scaffolds were fabricated by stereolithography using a photocurable resin based on the biocompatible, biodegradable and rubber-like material, poly(trimethylene carbonate) (PTMC). A numerical approach was developed to calculate the surface curvature distributions of the TPMS architectures. Moreover, the scaffolds were characterized by scanning electron microscopy, micro-computed tomography and water permeability measurements. These original scaffold architectures will be helpful to decipher the biofunctional role of the surface curvature of scaffolds intended for tissue engineering applications.